The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0004-282x2007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory groove meningiomas: surgical technique and follow-up review

Abstract: -Background: Olfactory groove meningiomas comprise 4-10% of the intracranial meningiomas. Generally they give signs of brain compression due to great size they reach before diagnosis. In this study, the clinical outcome of patients with olfactory groove meningiomas surgically treated was analyzed. Method: 17 patients operated on from 1988-2006. Follow-up: 1-209 months (mean=51.07±12.73. Bifrontal/bifrontal-bi-orbital approaches were used. Outcome was analyzed using survival/recurrence-free Kaplan-Mayer curves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
1
27
1
3
Order By: Relevance
“…They reported that a small frontolateral approach provided best results concerning visual outcomes than the pterional and subfrontal approaches, and similar results regarding rates of total tumor removal 20,21 . The results of gross total resection of anterior cranial fossa meningiomas reported in the literature, as well as ours (83.3%), obtained after minimally invasive approaches to these tumors have similar results to traditional craniotomy series 20,[22][23][24][25][26][27] . Recently, Reisch and Perneczky reported their experience using the supraorbital eyebrow approach for the treatment of 93 anterior and medial fossa meningiomas.…”
Section: Illustrative Casessupporting
confidence: 82%
“…They reported that a small frontolateral approach provided best results concerning visual outcomes than the pterional and subfrontal approaches, and similar results regarding rates of total tumor removal 20,21 . The results of gross total resection of anterior cranial fossa meningiomas reported in the literature, as well as ours (83.3%), obtained after minimally invasive approaches to these tumors have similar results to traditional craniotomy series 20,[22][23][24][25][26][27] . Recently, Reisch and Perneczky reported their experience using the supraorbital eyebrow approach for the treatment of 93 anterior and medial fossa meningiomas.…”
Section: Illustrative Casessupporting
confidence: 82%
“…They claimed that the frontolateral and pterional approaches provide remarkable improvement compared with the bifrontal approach. To decrease tumor recurrence, some authors recommend cranial base approaches such as uni or bilateral orbital osteotomy and cranial base drilling and reconstruction 2,5,8,16,25 . The demographic characteristics of the patients in this series did not influence the results.…”
Section: Surgical Approaches and Microsurgical Techniquesmentioning
confidence: 99%
“…OGMs are a subset of meningiomas that grows over the cribiform plate and the frontosphenoidal suture. They represent 8-18% of all intracranial meningiomas 1,2,3,4,5 . OGMs displace the optic nerve (ON) and the chiasm inferiorly and posteriorly.…”
mentioning
confidence: 99%
“…The differentiation from meningiomas of the planum sphenoidale and tuberculum sellae is of clinical and surgical importance; tumors arising from these sites are usually diagnosed at an early stage due to visual impairment, which is a late finding in OGMs (7,11,22,28).…”
Section: Introductionmentioning
confidence: 99%
“…This feature is rarely observed in planum █ INTRODUCTION O lfactory groove meningiomas (OGMs) account for 4-13% of all intracranial meningiomas. They originate from the dura of the anterior cranial fossa over the cribriform plate and frontosphenoidal suture (7,10,11,25,36).OGMs usually present with hypo/anosmia, visual deterioration, mental changes and headache as a result of olfactory or optic nerve and frontal lobe compression. Seizures are also common in these patients (8,33).…”
mentioning
confidence: 99%